Strategi Pembelajaran Kooperatif dalam Meningkatkan Motivasi Belajar Siswa - Natasya Nurul Lathifa; Khairil Anisa; Sri Handayani; Gusmaneli Gusmaneli (Lembaga Pengembangan Kinerja Dosen, 2024)
Cooperative learning has been known as an effective learning method in increasing student learning motivation. This research aims to present a literature review of cooperative learning strategies and their impact on student learning motivation. Cooperative learning methods involve interaction between students to achieve joint learning goals, thereby encouraging them to actively participate in the learning process. Literature studies show that cooperative learning strategies, such as team learning, pair learning, and group discussions, can increase student learning motivation through increasing a sense of responsibility, mutual trust, and cooperation between students. In addition, cooperative learning can also increase student involvement in the learning process, strengthen social relationships between students, and help students develop important social skills. The results of this literature review indicate that the implementation of cooperative learning strategies can make a positive contribution to student learning motivation. Therefore, it is recommended that educators consider using cooperative learning strategies in designing learning that can effectively increase student learning motivation.